Resonance phenomena in electron scattering by atomic oxygen from 9 to 11.4 eV - Wang, Y.; Zhou, Y.; Ratnavelu, K. (American Physical Society, 2010)
The momentum-space coupled-channels optical method has been used to study negative-ion resonance phenomena in electron impact on atomic oxygen in the energy region of 9-11.4 eV. Total scattering cross sections have been calculated, and negative-ion resonances have been located. Most of the known resonances of available experimental observations and theoretical results have been confirmed, and some new resonance features have been found in the present calculation.